Anak Jalanan di Kota Medan - Sinaga, M. Harwansyah Putra; Siregar, Afnita Marni; Ritonga, Dahniar; Linri, Linri; Rambe, Nurul Zanna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Street children are primarily victims and a result of errors in the selection of a development model that has focused too much on growth and regional development in big cities.. Medan City is a metropolitan city in Indonesia facing the problem of a large number of street children. According to the Child Protection Regulation, the Medan Government stated that the number of street children in 2022 reached 550. Seeing the increasing number of street children in Medan and the various factors that cause children to become street children, the purpose of this research is to find out the background of street children choosing to work on the streets, the social relationships of street children, and the physical health of street children. The method used is quantitative descriptive research, which means this research describes a situation according to the actual events that can be interviewed, observed, and documented. Quantitative descriptive method is interpreted as a research method whose form of description is in numbers. From several locations in Medan City where children are used as places to earn money, in this research there are three points that are used as research locations, namely Pasar Raya MMTC, Terminal Aksara, and Alfamidi in Medan City. The results of the research show that poverty, parental pressure, social environment, low education, and the desire to have their own money are the factors behind street children in Medan. By working as street children, some street children have closed, indifferent, and lazy social relationships. The physical health of street children that the researcher observed shows that most street children experience skin irritation and are thin due to unhealthy eating patterns.